Liability for animals a comparative study: South African and German law - Müller, Stephanie (School For Advanced Legal Studies, 2026)
The field of' Liability for Animals' appears at first sight to be only of minor interest to academics. This, however, is a false syllogism as incidents involving animals are frequent, and courts constantly deal with claims regarding damages for injuries caused by animals. Indeed in many countries the law of animals forms a special subject. With respect to English law for instance Lord Simonds, using the metaphor of a train, remarked that the Common Law of torts has developed historically in separate compartments and that beasts have travelled in a compartment of their own. However, it is also true, that within this "tort-train" a few animals lurking in the other compartments marked 'Negligence or Nuisance' may also be found. Over the years the law of animals was subject to major developments.